Tłumaczki chleb powszedni. Ludmiła Marjańska i Mary Swann - Rajewska, Ewa (Poznańskie Studia Polonistyczne. Seria Literacka, 2018)
The article discusses a translation of a Carol Shields’s novel Swann. A Mystery (1987) by a Polish poet Ludmiła Marjańska (Zagadka wiecznego pióra, 1998). Marjańska’s translation is not an easy one to assess: it contains some shifts as well as simple mistakes, but Polish versions of lyrics quoted in the novel as written by a mysterious, unacknowledged (and non-existing) poet Mary Swann are undeniably its strongest point. What makes them more interesting, they show close affinity to poems by Emily Dickinson translated by Marjańska – and to her own poetry.